The real MCITP exam 647 Windows Server 2008 Enterprise Administrator prep kit - Azad, Tariq (Syngress Pub., 2008)
This exam is designed to validate skills as a Windows Server 2008 Enterprise Administrator. This exam will fulfill the Windows Server 2008 IT Professional requirements of Exam 70-647. The Microsoft Certified IT Professional(MCITP) on Windows Server 2008 credential is intended for information technology (IT) professionals who work in the complex computing environment of medium to large companies. The MCITP candidate should have at least one year of experience implementing and administering a network operating system in an environment that has the following characteristics: 250 to 5,000 or more users; three or more physical locations; and three or more domain controllers. A MCITP Enterprise Administrator is responsible for the overall IT environment and architecture, and translates business goals into technology decisions and designs mid-range to long-term strategies. The enterprise administrator is also responsible for infrastructure design and global configuration changes. * Targeted at MCSE/MCSA upgraders AND new MCITP certification seekers. * Interactive FastTrack e-learning modules help simplify difficult exam topics * Two full-function ExamDay practice exams guarantee double coverage of all exam objectives * Free download of audio FastTracks for use with iPods or other MP3 players * THE independent source of exam day tips, techniques, and warnings not available from Microsoft * Comprehensive study guide guarantees 100% coverage of all Microsoft's exam objectives.